Description Level of Nomophobia Tendency in Adolescent Children at Junior High School in Bandung - Apriliani, Annisa; Rakhmawati, Windy; Kosim, Kosim (Indonesian Journal of Global Health Research, 2024)
The development of technology such as smartphones is growing rapidly which can facilitate teenagers activities to be easier. The convenience provided can increase a sense of dependence and cause adolescents to tend to nomophobia. Nomophobia (No Mobile Phone Phobia) is a modern phobia characterized by fear and anxiety due to not being with a smartphone. This study aims to determine how the level of nomophobia tendency in adolescent children in Bandung middle school. The study used descriptive quantitative method with cross sectional design. The population in this study were students of SMPN Bandung grades VII, VIII, and IX totaling 928 students. The sampling technique used was proportional stratified random sampling with a sample of 99. Determination of the sample from each class will be done randomly using the wheels of names application through the absentee number. Data were obtained through a questionnaire in the form of google forms distributed online. The instrument used is Nomophobia Questionnaire (NMP-Q) made by (Yildirim & Correia, 2015) consisting of 20 questions with the results of the validity test r count of 0.468 – 0.754 (r table = 0.195 ) and Cronbach’s alpha results of 0.945. Univariate analysis was used in this study with frequency distribution and percentage. The results showed that most of the respondents 62 people (62.6%) showed moderate nomophobia tendencies, 36 people (36.4%) showed mild nomophobia tendencies and 1 person (1%) did not experience nomophobia tendencies. There were no respondents who showed severe nomophobia tendencies. Most of the respondents belonged to the moderate nomophobia tendency category. Therefore, it is hoped that nurses can make efforts to deal with nomophobia in the form of health education, REBT self management techniques, and KEKINIAN family.